The new solitary wave structures for the (2 + 1)-dimensional time-fractional Schrodinger equation and the space-time nonlinear conformable fractional Bogoyavlenskii equations - Md Nur Alam; Cemil Tunç (Alexandria Engineering Journal, 2020)
The present paper employs the space-time fractional nonlinear Bogoyavlenskii equation and Schrodinger equation. We perform a new method to take some new solitary wave phenomena for each equation. Those solutions can explain through hyperbolic, trigonometric and rational functions. The graphical design makes the dynamics of the equations noticeable. Herein, the intended approach is simplistic, conventional, and convenient in implementing many solitary wave phenomena of several nonlinear fractional wave equations occurring in mathematical physics and engineering as well.